Good Practice Example and a Success Story from the European Commission - Theocharous, Antonis L. (My University, 2026)
Good Practice Example and a Success Story from the European Commission “SmartFarmer: Improving skills for SmartFarming as an innovative tool for rural development and economic growth”. Awarded by European Project Leonardo da Vinci (LdV)-Transfer of Innovation (TOI) project
Keywords: Sciences